Distal embolization at the site of a stenotic distal anastomosis of a saphenous vein graft, leading to dye entrapment - Toutouzas, Konstantinos; Kostov, Jorgo; Colombo, Antonio (Informa UK Limited, 2003)
This case report describes the entrapment of contrast media after recanalization of a recently occluded saphenous vein graft with balloon predilation, thrombectomy and stent implantation. Recanalization of the respective coronary artery was performed, and the entrapped contrast media within the saphenous vein graft progressed to the left circumflex artery.